Competing public narratives in nutrition policy: insights into the ideational barriers of public support for regulatory nutrition measures - Katherine Cullerton; Dori Patay; Michael Waller; Eloise Adsett; Amanda Lee (BMC, 2022)
Abstract Background Enacting evidence-based public health policy can be challenging. One factor contributing to this challenge is a lack of public support for specific policies, which may stem from limited interest or conviction by policy arguments. This can happen when messaging strategies regarding policy do not resonate with the target group and/or policy narratives compete in public discourse. To understand how policy messaging can better resonate with a target audience, we examined the frames and narratives used by the Australian public when discussing nutrition policies. Methods We conducted 76 street intercept interviews in urban and regional settings in Queensland, Australia. Quantitative data were analysed using mean agreement scores and t-tests, and the qualitative data were analysed using an adapted qualitative narrative policy framework (QNPF). The QNPF is used to illustrate how competing narratives vary in the way they define different elements. These elements often include setting, characters, plot, policy solution and belief systems. Results Level of support for all nutrition policies was generally moderate to high, although nutrition policies perceived to be most intrusive to personal freedoms were the least popular among the public. The value of fairness was consistently invoked when participants discussed their support for or opposition to policy. Using the QNPF, two distinct settings were evident in the narratives: concern for the community or concern for self. Villains were identified as either "other individuals, in particular parents" or "Big Food". Victims were identified as "children" or "the food industry, in particular farmers". Frequently used plots focused on individuals making poor choices because they were uneducated, versus Big Food being powerful and controlling people and the government. Conclusions The study examined the frames and narratives used by the Australian public when discussing nutrition policies. By examining these frames and narratives, we gained insight into multiple strategies which may increase public support for certain nutrition policies in Australia.